Search for stable mutli-charged particles with the ATLAS experiment - Zimmermann Simone (EPJ Web of Conferences, 2013)
A search for long-lived, multi-charged particles is performed using the ATLAS detector. We examine pp collision-data taken during the 2011 LHC running, corresponding to an integrated luminosity of 4.4 fb−1. A search is made for charged particle tracks exhibiting anomalously high ionization consistent with stable massive particles with charges from |q| = 2e to |q| = 6e. For this search new variables of specific energy loss per path length (dE/dx) are developed and used in the candidate selection. No excess is observed with respect to the prediction of Standard Model processes. The 95% CL cross-section limits are interpreted as lower mass limits of 420-490 GeV for a simplified Drell-Yan production model.